Identification, Expression, and Interaction Analysis of Ovate Family Proteins in Populus trichocarpa Reveals a Role of PtOFP1 Regulating Drought Stress Response - Wang, Hemeng; Chen, Jin-Gui; Chang, Ying (Frontiers in Plant Science, 2021)
Ovate Family Proteins (OFPs) are a family of plant growth regulators that play diverse roles in many aspects of physiological processes. OFPs have been characterized in various plant species including tomato, Arabidopsis and rice. However, little is known about OFPs in woody species. Here, a total of 30 PtOFP genes were identified from the genome of Populus trichocarpa and were further grouped into four subfamilies based on their sequence similarities. Gene expression analysis indicated that some members of PtOFP gene family displayed tissue/organ-specific patterns. Analysis of cis-acting elements in the promoter, as well as gene expression by hormone treatment revealed putative involvement of PtOFPs in hormonal response. Furthermore, PtOFP1 (Potri.006G107700) was further experimentally demonstrated to act as a transcriptional repressor. Yeast-two-hybrid assay showed physical interactions of PtOFP1 with other proteins, which suggests that they might function in various cellular processes by forming protein complexes. In addition, overexpression of PtOFP1 in Arabidopsis conferred enhanced tolerance to PEG-induced drought stress at seedling stage, as well as a higher survival rate than the wild-type at mature stage. These results provide a systematic analysis of the Populus OFP gene family, and provide a foundation for functional characterization of this gene family.